Effects of Artemisia Vulgaris Extract on Apoptotic Index and Caspase-8 - Sugiharto, Jonathan; Selamat Budijitno (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Worldwide incidence of breast cancer is still high. Surgical intervention is mainly used as primary treatment with other supplementary modality such as chemoterapy, radioterapy, and immunotherapy such as Artemisia vulgaris (AV). This study was aimed to analyze the increase in apoptotic effect response of adriamycin-cyclophosphamide on C3H mice model of adenocarcinoma breast cancer provided with Artemisia vulgaris extract. Methods. This research is a post-test only control group design. Twenty four C3H mice were randomly selected and put into 4 groups: K (control group), P1 (Chemoterapy only), P2 (extract only) and P3 (chemoterapy-extract combination). Breast adenocarcinoma was taken from inoculated donor mice. Chemoterapy regiment of 0.18 mg Adriamycin and 1.8 mg Cyclophosphamide were given in 2 cycles. Thirteen miligrams (0.2 mL) of AV extract was given orally once daily. Apoptotic index and Caspase-8 expression were graded with immunohistochemistry stain. Results. Mean value of p53 and caspase-8 expression in K, P1, P2, P3 groups were 22,06 + 1,73, 37,16 + 1,20, 24,60 + 1,08, 39,78 + 1,19 and 17.16 + 1,28, 26,20 + 1,11, 24.60 + 1,08, 39,78 + 1,19, respectively. Statistical analysis showed significant differences in apoptotic index between group K vs P1, P3 (p = 0,001), P1 vs P2 (p = 0,001), P1 vs P3 (p = 0,035), P2 vs P3 (p = 0,001) and for Caspase-8 between K vs P1, P3 (p = 0,001), K vs P2 (p = 0,048), P1 vs P2 (p = 0,001), P1 vs P3 (p = 0,039), P2 vs P3 (p = 0,001). We found a significant correlation between apoptotic index and Caspase-8 expression. (p = 0,047 and r = 0,883). Conclusion. Artemisia vulgaris can increase the adriamycin-cyclophosphamide chemoterapy effectiveness on C3H Mice Model of Breast Adenocarcinoma.